1996
DOI: 10.1126/science.271.5252.1086
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Evolution of Catalysis

Abstract: The germline genes used by the mouse to generate the esterolytic antibody 48G7 were cloned and expressed in an effort to increase our understanding of the detailed molecular mechanisms by which the immune system evolves catalytic function. The nine replacement mutations that were fixed during affinity maturation increased affinity for the transition state analogue by a factor of 10 4 , primarily the result of a decrease in the dissociation rate of the hapten-antibody complex. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
159
1
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(176 citation statements)
references
References 61 publications
10
159
1
6
Order By: Relevance
“…Abs specific for a foreign molecule may then be evolved when a rapid change in concentration or presentation of the foreign molecule triggers a mutagenic proliferation of the germ-line Ab (12,13). During this process, known as somatic evolution, mutations may be selected that simultaneously increase affinity and selectivity if they act, at least in part, to restrict the Ab to a conformation that is appropriate for recognition of the foreign molecule (8,10,11,(14)(15)(16)(17)(18)(19)(20)(21). The resulting Abs are specific for their foreign targets and thus may be produced at increased levels without risk of self-recognition and autoimmunity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Abs specific for a foreign molecule may then be evolved when a rapid change in concentration or presentation of the foreign molecule triggers a mutagenic proliferation of the germ-line Ab (12,13). During this process, known as somatic evolution, mutations may be selected that simultaneously increase affinity and selectivity if they act, at least in part, to restrict the Ab to a conformation that is appropriate for recognition of the foreign molecule (8,10,11,(14)(15)(16)(17)(18)(19)(20)(21). The resulting Abs are specific for their foreign targets and thus may be produced at increased levels without risk of self-recognition and autoimmunity.…”
mentioning
confidence: 99%
“…Germ-line Abs are assembled from a set of known genomic fragments, which may be determined by comparing the 5Ј UTR of candidate genomic fragments with that of the rearranged genes (17). Mutations identified by comparing these sequences are typically found throughout the Ab-combining site, which is formed from the six loops or complementarity-determining regions (CDRs) that connect the strands of the ␤-sheet framework (Fig.…”
mentioning
confidence: 99%
“…2a), systematic somatic mutagenesis of these positions in the UCA via affinity maturation may preconfigure the HCDR3 loop into the HAbound conformation. This dependency on the affinity-maturation state of the antibody, independent of the HCDR3 loop, has also been observed for the esterolytic antibody 48G7 (Patten et al, 1996;Wedemayer et al, 1997). These studies showed that the affinitymatured 48G7 antibody has a 30 000-fold higher affinity for haptens compared with its germline precursor.…”
Section: Resultsmentioning
confidence: 48%
“…The possibility that mutated residues are actually in contact with the antigen epitope(s) in the antibody-antigen complex structure should be investigated further using techniques, such as site-directed mutagenesis and molecular modeling. In the case of protein antigens, it has not yet been known that somatic mutations distal from the contact sites of antibodies have a functional role, although somatic hypermutations occurred in non-contact residues of antibodies for small haptenic antigens (Chien et al, 1989;Strong et al, 1991;Patten et al, 1996).…”
Section: Discussionmentioning
confidence: 99%